Probing Local Electronic Transitions in Organic Semiconductors through Energy‐Loss Spectrum Imaging in the Transmission Electron Microscope. (2nd September 2015) - Guo, Changhe; Allen, Frances I.; Lee, Youngmin; Le, Thinh P.; Song, Chengyu; Ciston, Jim; Minor, Andrew M.; Gomez, Enrique D.
Abstract : Improving the performance of organic electronic devices depends on exploiting the complex nanostructures formed in the active layer. Current imaging methods based on transmission electron microscopy provide limited chemical sensitivity, and thus the application to materials with compositionally similar phases or complicated multicomponent systems is challenging. Here, it is demonstrated that monochromated transmission electron microscopes can generate contrast in organic thin films based on differences in the valence electronic structure at energy losses below 10 eV. In this energy range, electronic fingerprints corresponding to interband excitations in organic semiconductors can be utilized to generate significant spectral contrast between phases. Based on differences in chemical bonding of organic materials, high‐contrast images are thus obtained revealing the phase separation in polymer/fullerene mixtures. By applying principal component analysis to the spectroscopic image series, further details about phase compositions and local electronic transitions in the active layer of organic semiconductor mixtures can be explored. Abstract : Monochromated transmission electron microscopes can generate contrast in organic thin films based on differences in the valence electronic structure at energy losses below 10 eV. By applying principal component analysis to the spectroscopic image series, further details about phase compositions and local electronic transitions in the active layer of organic semiconductor mixtures can be explored.